Reporter cell assay-based functional quantification of TNF-α-antagonists in serum: a proof-of-principle study for adalimumab - Schuster, Lukas; Sauter, Max; Uhl, Philipp; Meid, Andreas; Haefeli, Walter E.; Weiß, Johanna; Theile, Dirk (Analytical biochemistry, 2020)
Quantification of therapeutic antibodies is commonly based on physico-chemical assays such as enzyme-linked immunoabsorption assays (ELISA) and lately on mass spectrometry. However, the functional integrity of evaluated immunoglobulins is yet not assessed. Consequently, a commercially available reporter cell line was used to quantify the functional concentration of the anti-tumor necrosis factor alpha (TNF-α) antibody adalimumab present in serum of a healthy beagle dog treated with 3 mg intravenous adalimumab (Humira®). HEK-Blue™-hTLR3 cells express a secreted alkaline phosphatase under the control of a nuclear factor kappa B (NF-κB) response element. Its enzymatic activity can be recorded using colorimetry, which reports activity of extracellular NF-κB stimuli such as TNF-α. Using an adalimumab concentration-response calibration curve, the functional concentration of serum adalimumab was estimated to be 4.9 ± 1.4 μg/ml, which was in excellent agreement with ELISA results (4.8 μg/ml). The obtained data suggest that this simple, easy-to-handle reporter cell assay can be used for the functional quantification of adalimumab present in samples from in vitro or pre-clinical in vivo experiments. Moreover, this assay could be used in vitro to compare the pharmacodynamics of adalimumab biosimilars or different anti-TNF-α compounds, respectively.